Fibroblasts of Machado Joseph Disease patients reveal autophagy impairment - Onofre, Isabel (2016)
Machado Joseph Disease (MJD) is the most frequent autosomal dominantly inherited cerebellar ataxia caused by the over-repetition of a CAG trinucleotide in the ATXN3 gene. This expansion translates into a polyglutamine tract within the ataxin-3 protein that confers a toxic gain-of-function to the mutant protein ataxin-3, contributing to protein misfolding and intracellular accumulation of aggregates and neuronal degeneration. Autophagy impairment has been shown to be one of the mechanisms that contribute for the MJD phenotype. Here we investigated whether this phenotype was present in patient-derived fibroblasts, a common somatic cell type used in the derivation of induced pluripotent stem cells and subsequent differentiation into neurons, for in vitro disease modeling. We generated and studied adult dermal fibroblasts from 5 MJD patients and 4 healthy individuals and we found that early passage MJD fibroblasts exhibited autophagy impairment with an underlying mechanism of decreased autophagosome production. The overexpression of beclin-1 on MJD fibroblasts reverted partially autophagy impairment by increasing the autophagic flux but failed to increase the levels of autophagosome production. Overall, our results provide a well-characterized MJD fibroblast resource for neurodegenerative disease research and contribute for the understanding of mutant ataxin-3 biology and its molecular consequences.